Diagnosing the condition of the trees computed tomography in Historic LINDEN avenue in Krasienin (Lublin province) - Durlak, Wojciech; Dudkiewicz, Margot; Pudelska, Krystyna; Dąbski, Marek (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
The aim of the study is to assess the condition of selected trees in the old linden avenue in Krasienin, which is the access road to the nineteenth-century classicist manor house of Mrozewiczów. Linden alley determines the main axis of the assumptions and with the object. Manor park is entered in the register of monuments lubelskie province. Assessment of linden was based on the external appearance of the trees, and using the device Picus Sonic Tomograph allows to precisely determine the quality of a copy of the structure of wood in the tested cross-section. The results show that the state of health of trees selected for evaluation in the historic avenue of lime is varied. Most of July is characterized by reduced health condition. Computed tomographic images showed that more than half of the trees involved wood completely technically operable ranges from 37 to 42% and the minimum wall thickness is more than 15 cm. This does not mean, however, that the trees can be considered safe in terms of stability (mechanical strength). To a large extent this depends on the degree of decomposition of the wood inside the trunk and the method of its location. On the two specimens was observed fruiting bodies of fungi: Panellus stipticus and Pleurotus ostreatus. The worst condition is lime with inv. 72, which has a residual amount of wood is fully operational and copy threatening traffic safety. It is recommended its removal.